Students’ Attitudes Towards Using Mobile Applications in Learning English Listening Skills at Ho Chi Minh City University of Foreign Languages and Information Technology - Thuong, Le Hoang Thai; Tham, Duong My (VNU Journal of Science: Education Research; Vol 39 No 2DO - 10.25073/2588-1159/vnuer.4703, 2023)
Technology continues to create new avenues for inspiring language learners. unlocking the vast potential of technology requires institutions, teachers, students, and communities to collaborate to determine how it can be optimally implemented in a particular setting. This study aimed to determine how sophomores majoring in English at Ho Chi Minh City University of Foreign Languages and Information Technology thought about using mobile applications through mobile devices to improve their English listening skills. One hundred and one English major students at Ho Chi Minh City University of Foreign Languages and Information Technology participated in the mixed-methods study. Using the mixed-methods research design with a survey questionnaire as the primary data collecting instrument, the study obtained significant findings and accomplished its objectives. The study findings indicate that the majority of participants had positive sentiments regarding the use of mobile applications inside and outside the classroom. This study also revealed that most English majors agreed that listening practice through mobile applications could improve their listening skills. In addition, although the participants accepted that the mobile devices contained a lot of distractions while using, they still held positive attitudes towards the use of mobile applications and continued using them to practice their English listening skills.